PERSPEKTIF POLITIK HUKUM PERUNDANG-UNDANG & HUKUM ISLAM PERKAWINAN DIBAWAH UMUR - Army Setyo Wibowo; Tubagus Deni Sunnardi; Sulistiyono Catur (Universitas Muhammadiyah Jember, 2021)
The high rate of early marriage in Talagasari Village, Kadungora Garut District. Make local government intervene and move quickly in dealing with underage marriages. Because underage marriages are considered one of the increasing numbers of divorce. Departing from this background, the composer wants to take the following main issues. What are the efforts made by the Talagasari Village Government in reducing the number of underage marriages. And what is the perspective of the law and Islamic law about marriages under age. This type of research research used is field research. That is aimed at solving problems by telling, analyzing, and classifying. The results of research in the village of Talagasari concluded that the efforts of the local government in reducing the number of underage marriages by 1). Conducting socialization and educating the public about the impact by presenting experts in the field.